Movie Review “The Firm (1993)”, Director: Sydney Pollack, Written by: David Rabe, Robert Towne, David Rayfiel, Daniel Pyne. Production: Paramount Pictures (Universitas Negeri Semarang, 2022)
The Firm is a 1993 American legal thriller film directed by Sydney Pollack and starring Tom Cruise, Jeanne Tripplehorn, Gene Hackman, Ed Harris, Holly Hunter, Hal Holbrook, and David Strathairn. The film is based on the 1991 novel The Firm by author John Grisham. A young lawyer joins a small but prestigious law firm only to find out that most of their clients are on the wrong side of the law. The company is helping to launder mob money, get clients off charges and even murder partners who threaten to blow their cover, but when the FBI come calling to gather evidence on the lawyer's colleagues, he is caught between a rock and a hard place, juggling his life and his liberty.